2002
DOI: 10.1021/es020656n
|View full text |Cite
|
Sign up to set email alerts
|

The West Falmouth Oil Spill after Thirty Years:  The Persistence of Petroleum Hydrocarbons in Marsh Sediments

Abstract: The long-term fate of petroleum hydrocarbons in marsh sediments (West Falmouth, MA) contaminated in 1969 by the spill of the barge Florida was investigated. A 36-cm-long sediment core was collected in August 2000, and sediment extracts were analyzed by gas chromatography (GC) and comprehensive two-dimensional gas chromatography (GC x GC). The latter technique is capable of separating 1 order of magnitude more compounds than the former and was used to observe whether any compositional changes in the unresolved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
182
0
9

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 301 publications
(202 citation statements)
references
References 42 publications
11
182
0
9
Order By: Relevance
“…Despite slight differences in analytical methods, the concentrations of residual total petroleum hydrocarbons (TPHs) within the 8 to 20 cm layer, for sediment collected in 2000, were in roughly the same range as those measured in 1973 in surface sediments (Reddy et al, 2002). The petroleum hydrocarbons present at depth are moderately degraded: volatile and water-soluble compounds and nalkanes have been removed, concentrations of acyclic isoprenoids have been reduced, but alkyl cyclohexanes, alkylbenzenes, and polycyclic aromatic hydrocarbons (PAHs) as well as many other unidentified hydrocarbons still persist (Reddy et al, 2002;Frysinger et al, 2003;White et al, 2005). In particular, total PAHs (mostly alkylated naphthalenes and phenanthrenes/anthracenes) in a core collected in 2000 were 134 _g g -1 in the 14-16 cm horizon (White et al, 2005b); such levels are very similar to concentrations of PAHs found in the 1970s (Blumer and Sass, 1972).…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…Despite slight differences in analytical methods, the concentrations of residual total petroleum hydrocarbons (TPHs) within the 8 to 20 cm layer, for sediment collected in 2000, were in roughly the same range as those measured in 1973 in surface sediments (Reddy et al, 2002). The petroleum hydrocarbons present at depth are moderately degraded: volatile and water-soluble compounds and nalkanes have been removed, concentrations of acyclic isoprenoids have been reduced, but alkyl cyclohexanes, alkylbenzenes, and polycyclic aromatic hydrocarbons (PAHs) as well as many other unidentified hydrocarbons still persist (Reddy et al, 2002;Frysinger et al, 2003;White et al, 2005). In particular, total PAHs (mostly alkylated naphthalenes and phenanthrenes/anthracenes) in a core collected in 2000 were 134 _g g -1 in the 14-16 cm horizon (White et al, 2005b); such levels are very similar to concentrations of PAHs found in the 1970s (Blumer and Sass, 1972).…”
mentioning
confidence: 77%
“…The oiled sediments are now overlain by subsequent accretion, about 0.35 cm yr -1 , of salt marsh sediments devoid of oil (White et al, 2005a). Despite slight differences in analytical methods, the concentrations of residual total petroleum hydrocarbons (TPHs) within the 8 to 20 cm layer, for sediment collected in 2000, were in roughly the same range as those measured in 1973 in surface sediments (Reddy et al, 2002). The petroleum hydrocarbons present at depth are moderately degraded: volatile and water-soluble compounds and nalkanes have been removed, concentrations of acyclic isoprenoids have been reduced, but alkyl cyclohexanes, alkylbenzenes, and polycyclic aromatic hydrocarbons (PAHs) as well as many other unidentified hydrocarbons still persist (Reddy et al, 2002;Frysinger et al, 2003;White et al, 2005).…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…While petroleum hydrocarbons themselves are rich source of organic carbon and are readily biodegradable [19], particularly under aerobic conditions, their extreme hydrophobicity and low solubility [20][21][22][23] complicates accurate predictions of natural attenuation rates. One potentially critical factor governing persistence in coastal environments that has generally been overlooked in models is geometry of the contaminant source.…”
Section: Role Of Geometry In 'Fate and Persistence'mentioning
confidence: 99%
“…It is known to cause significant shifts in microbial communities of oceans and coasts [14, 17, 56, 57] and negatively impacts most of the higher life forms [5,7,16,22,23,49,58].…”
Section: Oil Spills and Petroleum Contaminationmentioning
confidence: 99%